The effects of social influence and financial literacy on savings behaviour: a study on college students in Kota Kinabalu, Sabah - Amer Azlan Abdul Jamal; Wijaya Kamal Ramlan; Mohd Rahimie Abdul Karim; Rosle Mohidin; Zaiton Osman (2015)
Economists generally believe that higher savings will spur economic growth, thus strengthening the economy further. In Malaysia however, the sharp increase in the ratio of household debt to disposable income particularly over the past ten years has raised doubts on the ability of Malaysians to save and plan for their future. As a result, total household savings remained low and there is high risk that Malaysians would not have sufficient savings for their retirement. Even more worrying is that young adults reportedly are the main group who are trapped into this financial difficulty. The issue has raised concern on the needs to educate young Malaysian adults on the fundamental importance of savings in order to ensure financial sufficiency on their retirement. With regards to savings behavior, the needs for savings are different amongst individuals due to different mind-set, behavior, knowledge, and social environment. This study intends to explore the savings behavior amongst students of higher learning institutions in Kota Kinabalu, Sabah. Specifically, the study intends: (i) to investigate the determinants of savings behavior; and, (ii) to examine the mediating effect of attitude towards the relationship between financial literacy and savings behavior. Data was collected using structured questionnaire and analyzed using SMART-PLS, a second generation structural equation modelling software. The results indicate that family involvement plays a major role in nurturing students’ savings behavior, followed by financial literacy and peer influence. In addition, students are said to have more favorable financial attitude when they are financially literate. Financial attitude however, does not mediate the relationship between financial literacy and savings behavior. This research is expected to contribute to the body of knowledge within the financial wellness and personal financial planning context.